Analisis Rentabilitas Bank Syariah Saat Pandemic Covid-19 Di Indonesia - Umi Sakdiyah; Rizal Fahlevi (At-Tamwil: Journal of Islamic Economics and Finance, 2023)
The purpose of this study was to find out how much influence ROA, NPF and BOPO had on NOM of Islamic banks before and during the covid-19 pandemic. This study applies a quantitative method with secondary data types obtained from financial statements of Islamic banks in the form of time series. The results of the study show that the effect of ROA before the pandemic is smaller than during the pandemic, meaning that the ability of Islamic bank management to earn profits during the pandemic has decreased overall. NPF has a very big influence during a pandemic, meaning that there is an increase in problem financing due to the impact of Covid-19 which has affected the economic sector. BOPO has no influence during a pandemic, meaning that management is able to reduce operational costs, this occurs because during a pandemic operational management switches to using an internet technology system which can reduce operational costs rather than a manual system. Simultaneously, ROA, NPF and BOPO both have an influence on the NOM of Islamic banks, the influence during a pandemic is greater than before the pandemic, this occurs because the NPF variable relating to problem financing during a pandemic is very large.